LATE HOLOCENE EARTHQUAKES IN SOUTHERN APENNINE: PALEOSEISMOLOGY OF THE CAGGIANO FAULT - Galli P.; Bosi V.; Piscitelli S.; Giocoli A.; Scionti V. (My University, 2006)
Although southern Apennines are characterized by the strongest crustal earthquakes of central-western Mediterranean region, local active tectonics is still poorly known, at least for seismogenic fault-recognition is concerned. Research carried out in the Maddalena Mts. (southeast of Irpinia, the region struck by the M w=6.9, 1980 earthquake) indicates historical ruptures along a 17-km-long, N120° normal fault system (Caggiano fault). The system is characterized by a bedrock fault scarp carved in carbonate rocks, which continues laterally into a retreating and eroded smoothed scarp, affecting the clayey-siliciclastic units, and by smart scarps and discontinuous free-faces in Holocene cemented slope-debris and in modern alluvial fan deposits. The geometry of the structure in depth has been depicted by means of electrical resistivity tomography, while paleoseismic analysis carried out in three trenches revealed surface-faulting events during the past 7 ky BP (14C age), the latest occurred in the past 2 ky BP (14C age) and, probably, during/after slope-debris deposition related to the little ice age (~1400–1800 a.d.). Preliminary evaluation accounts for minimum slip rates of 0.3–0.4 mm/year, which is the same order of rates estimated for many active faults along the Apennine chain. Associated earthquakes might be in the order of M w=6.6, to be compared to the historical events occurred in the area (e.g., 1561 and 1857 p.p. earthquakes).
Keywords: PALEOSEISMOLOGY; ACTIVE TECTONICS; HISTORICAL SEISMICITY; SEISMIC HAZARD; ITALY; Holocene; Cenozoic::Quaternary::Holocene; Кайнозой::Четвертичная::Голоцен